Lung deposition of nebulised pentamidine in children. Issue 3 (March 1993) - O'Doherty, M J; Thomas, S H; Gibb, D; Page, C J; Harrington, C; Duggan, C; Nunan, T O; Bateman, N T
Abstract : BACKGROUND: Nebulised pentamidine is effective for preventing Pneumocystis carinii pneumonia in adults with acquired immunodeficiency syndrome. The nebuliser dose required to produce equivalent lung concentrations of pentamidine in children is unknown. This study was performed to measure pulmonary pentamidine deposition in children and to relate this to age, ventilation pattern, and body size. METHODS: Nebulised pentamidine (50 mg in 6 ml saline) was administered to 12 children (including one with lymphocytic interstitial pneumonitis) and to six adults with human immunodeficiency virus infection using a Respirgard II nebuliser. Technetium-99m labeled colloidal human serum albumin was used as an indirect marker for pentamidine and deposition in the lungs was detected by a gamma camera. RESULTS: Absolute deposition of pentamidine was not related to age, height, weight, spirometry, or ventilation characteristics. Deposition, as a mean (SD) percentage of nebuliser output, was similar in children aged 8-11 years (5.5(2.4)%), teenagers aged 12-15 years (7.2(2.2)%) and adults (7.1(2.6)%). Aerosol concentration within the lungs (% nebuliser output deposited/predicted total lung capacity) was therefore higher in children (1.9(1.5)%/1) and teenagers (1.9(0.7)%/1) than in adults (1.0(0.7%)/1), and was negatively correlated with height (r = -0.69) and weight (r = -0.50). Deposition of aerosol in the region of the large central airways was particularly marked in children. Small reductions in forced expiratory volume in one second and forced vital capacity after treatment did not differ significantly between adults and children and visual analogue scores of subjective adverse effects did not vary with age. CONCLUSIONS: These results suggest that children probably require lower nebuliser pentamidine doses to produce lung pentamidine concentrations equivalent to those found to be effective for preventing P carinii pneumonia in adults using the Respirgard II nebuliser.